Understanding sepsis-induced immunosuppression and organ dysfunctions: from immunosuppression to immunotherapy - Dablu Lal Gupta; Tejprakash Sinha; Richa Pathak; Sanjeev Bhoi; D. N. Rao (Exploration of Immunology, 2022)
Sepsis is a life-threatening condition caused by dysregulated host immune response to infection, leading to persistent inflammation followed by immunosuppression. Sepsis represents a substantial global health problem owing to protracted inflammation, immune suppression, and susceptibility to nosocomial infections. Despite continuing progress in the development of antibiotics, fluid resuscitation, and other supportive care therapies, no specific immunomodulatory drugs or immunotherapeutic adjuncts for the treatment of sepsis are available to date. The advances in tertiary care facilities and patient care have improved the survival of sepsis patients in the initial hyper-inflammatory phase of sepsis. However, the majority of sepsis patients succumb later due to prolong immunosuppression. The sepsis-induced immune dysregulation and its long-term effects on mortality are under meticulous investigations that are still poorly defined. Sepsis leads to the impaired functions of the innate and adaptive immune systems. The exhaustion of T cells, reduced expression of human leukocytes antigen (HLA)-DR on monocytes, and induced uncontrolled apoptosis of immune cells have been reported as hallmark features of sepsis. Sepsis-induced immune cell apoptosis of immune cells is a primary contributing factor to the immunosuppression in sepsis. Preclinical studies have identified several new therapeutic targets for therapy in sepsis, including monoclonal antibodies (Abs) and anti-apoptotic agents to reduce T cells exhaustion, immune cells apoptosis, and restoring immune cells functions. Recent studies have centered on immune-modulatory therapy. The review article will focus solely on sepsis’ effects on innate and adaptive cells functions that contribute to immunosuppression. Finally, it is discussed how immune cells responsible for immunosuppression might be directly targeted to provide potential therapeutic benefits in treating sepsis and improving long-term survival.